STUDY OF OPTICALLY ACTIVE CENTERS IN DIAMONDS FROM URALIAN PLACERS; AN ATTEMPT TO LOCATE THEIR PRIMARY DEPOSITS - Khachatryan G.K.; Zinchuk N.N.; Koptil V.I.; Gurkina G.A.; Kharrasov M.K. (My University, 2004)
Placer diamonds from the North (Vishera) and Central (Koivo-Vizhai) Urals, whose primary deposits are still unknown, were studied by IR spectroscopy. There is a relationship between the internal structure of diamonds and the content of structural nitrogen and hydrogen impurities in them. Diamonds from the Vishera and Koivo-Vizhai regions differ significantly from each other in the type of distribution of A-centers and the degree of nitrogen aggregation. This evidences that they formed from different (though of the same type) sources. Comparison of the contents of optically active centers in the studied crystals and rounded diamond crystals from other deposits shows that the Uralian placer diamonds are of kimberlite genesis.
Keywords: DIAMOND; IR SPECTROSCOPY; OPTICALLY ACTIVE CENTERS